1990
DOI: 10.1007/bf01644177
|View full text |Cite
|
Sign up to set email alerts
|

A study on delta virus infection and its clinical impact in Iran

Abstract: During the period 1986-1988, the expression of anti-HDV in different high-risk groups and its clinical impact on patients with HBV-related chronic liver disease and hepatocellular carcinoma was investigated in Iran. Using the ELISA technique, we observed a 2.5% anti-HDV positivity in asymptomatic chronic HBsAg carriers (3 of 120); in hemophiliacs, two of six HBsAg carriers were positive for anti-HDV and zero of 50 anti-HBs positives. Anti-HBs positive dialysis patients were positive for anti-HDV in 2.0% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 30 publications
0
23
2
Order By: Relevance
“…Ninety-six articles were found in the literature review, 40 of which [4][10][11][12][13][15][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were potentially related to HDV prevalence in Iran. The detailed search process is demonstrated in Diagram 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ninety-six articles were found in the literature review, 40 of which [4][10][11][12][13][15][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] were potentially related to HDV prevalence in Iran. The detailed search process is demonstrated in Diagram 1.…”
Section: Resultsmentioning
confidence: 99%
“…After filtering the studies based on the inclusion criteria explained above, 19 studies were identified as assessing the prevalence of HDV infection in Iran. Out of these, four studies were conducted in Tehran [19][22][35][39], two studies in Shiraz and [10][45] Hamedan [21][23], and 1 each in the cities of Shahrekord [28], Mashhad [32], Khuzestan [33], Isfahan [24], Sari [11], Golestan [38], Babol [34], Bushehr [12], Kerman [50], and Tabriz [41]. Additionally, one study was carried out in both Tehran and Tabriz [44] Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, full-length HDV sequence analysis from Iran, where delta infection is endemic [16] and in some regions its prevalence reaches 14% among asymptomatic HBs carriers [17], has not been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…HDV prevalence rates of 0 to 19% occur in HBsAg carriers from Belgium, Germany, Hungary, Poland, Spain, Portugal, Yugoslavia, Norway, Jordan, Saudia Arabia, Yemen, Lebanon, Iran, and North India (23,156,162,176,204). In some countries, such as Italy, HDV endemicity is variable.…”
Section: Virus-encoded Proteinsmentioning
confidence: 99%